Diseño del modelo de gestión integrado NTC ISO 9001: 2015 y decreto 1072 del 2015 para manufactura elegancia con calidad S.A.S (M.E.C) (2017)
Manufacturas Elegancia Con Calidad (M.E.C) is a micro-enterprise of garments that over time has taken force in the industry for the quality of its products, but it requires to ensure its continuous improvement in all its aspects, considering the required legal. Taking into account the above, there are many applicable rules for this organization, it will take as basis of integration the NTC ISO 9001: 2015, focused towards the satisfaction of the interested parties and the Decree 1072 of 2015 that poses the Health and Safety System in the Work, supported by the minimum standards of the SG-SST described in Resolution 1111 of 2017. The design of the Integrated Management System for the implementation of the mentioned standards will be consistent with the objectives and open to the integration of other standards required by the company, from which the question arises, is it possible to design an Integrated Management System for M.E.C based on the NTC ISO 9001: 2015 Decree 1072 of 2015 and which ensures sustainability towards the future?, this is really the problem raised in this work. Therefore, what is proposed for Manufactura Elegancia con Calidad (M.E.C) is to design an Integrated System of Quality, Safety and Health Management at Work adaptable to other standards using ISO 9001: 2015 and Decree 1072 of 2015, considering Resolution 1111 of 2017, with the aim of achieving the objectives and the desired competitiveness.